Erythrovirus B19 infection. (December 2017) - Flower, Barnaby; MacMahon, Eithne
Abstract: Erythrovirus B19 causes erythema infectiosum or fifth disease, also called slapped cheek syndrome, a common childhood exanthem. Erythema infectiosum is typically an acute, self-limiting, biphasic illness commencing with non-specific flu-like symptoms accompanying viraemia, followed by more specific signs of rash and/or arthropathy coinciding with seroconversion. Most infections are subclinical. Erythrovirus B19 can cause life-threatening illness requiring urgent intervention, depending on age, immune and haematological status. Infection of nucleated red cells causes transient aplastic crisis in patients with haemoglobinopathies, and chronic anaemia in immunocompromised individuals. Up to 50% of women of childbearing age are susceptible, being at risk of fetal loss and hydrops fetalis if infected in the first 20 weeks of pregnancy. Diagnosis depends on the timing and nature of presentation. Aplastic crisis or red cell aplasia presents in the initial viraemic phase, warranting detection by polymerase chain reaction. In patients with rash or arthropathy, specific immunoglobulin M (IgM) and IgG testing is appropriate; IgG testing establishes susceptibility. No antivirals or preventive vaccines are available, but infection control, blood transfusion, intravenous immunoglobulin and reduction of immunosuppression play an important role in management. Infection control is a challenge as index cases are infectious for 10 days before onset of the rash.